2020
DOI: 10.1101/2020.05.28.120212
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CREBBPandSTAT6co-mutation and 16p13 and 1p36 loss define the t(14;18)-negative diffuse variant of follicular lymphoma

Abstract: The diffuse variant of follicular lymphoma (dFL) is a rare variant of FL lacking t(14;18) that was first described in 2009. In this study, we use a comprehensive approach to define unifying pathologic and genetic features through gold-standard pathologic review, FISH, SNP-microarray and next-generation sequencing of 16 cases of dFL. We found unique morphologic features, including interstitial sclerosis, microfollicle formation, and rounded nuclear cytology, confirmed absence of t(14;18) and recurrent deletion … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 60 publications
(105 reference statements)
2
4
1
Order By: Relevance
“…STAT6 mutation has been found to be enriched in selected series of FL with diffuse growth pattern, CD23 expression, and/or absence of t(14;18). [36][37][38][39] Our analysis identifies the FL_STAT6 cluster independent of such criteria but sharing associated molecular features, providing further evidence for this as a distinct molecular subtype of FL. In these prior studies of FL enrichment of STAT6 with CREBBP and TNFRSF14 mutation has been a consistent finding which is shared with our analysis.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…STAT6 mutation has been found to be enriched in selected series of FL with diffuse growth pattern, CD23 expression, and/or absence of t(14;18). [36][37][38][39] Our analysis identifies the FL_STAT6 cluster independent of such criteria but sharing associated molecular features, providing further evidence for this as a distinct molecular subtype of FL. In these prior studies of FL enrichment of STAT6 with CREBBP and TNFRSF14 mutation has been a consistent finding which is shared with our analysis.…”
Section: Discussionsupporting
confidence: 51%
“…We note that this does not exclude the potential for selective enrichment of STAT6 mutation among BCL2 translocation-negative FL, as has been previously reported, but argues that STAT6 mutation may occur as a feature of both BCL2 translocation-positive and -negative FL cases. [36][37][38][39] Mutational profiles in FL subgroups BIC clustering only on aSHM targets (excluding BCL2) confirmed the segregation based on these features alone, supporting the conclusion that a significant subset of FL is characterized by a mutational pattern consistent with higher aSHM activity. Seeking further evidence of differential mutational mechanisms between FL subsets, we carried out a mutational signature analysis.…”
Section: Fl Genetic Subclusterssupporting
confidence: 59%
“…In this study, we performed a genetic analysis of the largest series of t(14;18) 2 FL reported to date, with previous studies limited by a low number of cases 6,21 or focused on cases with BCL2 expression 11 or particular morphological features. [20][21][22]33 We found that t(14;18) 2 FL is genetically a heterogeneous disease that is most common in women, usually presents in early clinical stages (stages I/II) at diagnosis, and has an excellent prognosis. Morphologically, cases with a pure follicular growth pattern predominated (60%), although a diffuse component was frequently observed (40%).…”
Section: Discussionmentioning
confidence: 90%
“…Independent variables for cluster analysis patterns, either alone 20,33 or with the expression of CD23 21 or the presence of 1p36 deletion. 22 In the present study, we did not preselect the cases according to morphological characteristics and included all cases with a lack of t( compared with previous studies.…”
Section: A1mentioning
confidence: 99%
“…For example, TP53:KRAS co-mutation in NSCLC was found to confer clinical benefit to PD-1 inhibitors [7]. CREBBP:STAT6 co-mutation supports the diagnosis of the diffuse variant of follicular lymphoma [8]. NSCLC patients with EGFR:TP53 or EGFR:PIK3CA co-mutation are more likely to be resistant to the first-generation EGFR tyrosine kinase inhibitors [9].…”
Section: Introductionmentioning
confidence: 99%